Injury mortality in South Africa: a 2009 and 2017 comparison to track progress to meeting sustainable development goal targets - Megan Prinsloo; Shibe Mhlongo; Rifqah A. Roomaney; Lea Marineau; Thakadu A. Mamashela; Bianca Dekel; Debbie Bradshaw; Lorna J. Martin; Carl Lombard; Rachel Jewkes; Naeemah Abrahams; Richard Matzopoulos (Taylor & Francis Group, 2024)
Background Injuries, often preventable, prompted urgent action within the United Nations' 2030 Agenda for Sustainable Development Goals (SDGs) to improve global health. South Africa (SA) has high rates of injury mortality, but accurate reporting of official national data is hindered by death misclassification. Objective Two nationally representative surveys for 2009 and 2017 are utilised to assess SA's progress towards SDG targets for violence and road traffic injuries, alongside changes in suicide and under-5 mortality rates for childhood injuries, and compare these estimates with those of the Global Burden of Disease for SA. Methods The surveys utilised multi-stage, stratified cluster sampling from eight provinces, with mortuaries as primary sampling units. Post-mortem files for non-natural deaths were reviewed, with additional data from the Western Cape. Age-standardised rates, 95% confidence intervals (CIs), and incidence rate ratios (IRRs) were calculated for manner of death rate comparisons and for age groups. Results The all-injury age-standardised mortality rate decreased significantly between 2009 and 2017. Homicide and transport remained the leading causes of injury deaths, with a significant 31% decrease in road traffic mortality (IRR = 0.69), from 36.1 to 25.0 per 100 000 population. Conclusions Despite a reduction in SA's road traffic mortality rate, challenges to achieve targets related to young and novice drivers and male homicide persist. Achieving SA's injury mortality SDG targets requires comprehensive evaluations of programmes addressing road safety, violence reduction, and mental well-being. In the absence of reliable routine data, survey data allow to accurately assess the country's SDG progress through commitment to evidence-based policymaking.